Pattern of Regional Metasteses in Laryngeal Carcinoma - Ahsan, Ali Imam; Tarafder, Kamrul Hasan; Rahman, Sheikh Hasanur; Jamal, Nasimul; Ali, Syed Farhan; Yusuf, Md Abdullah; Sarwar, SM (Journal of Shaheed Suhrawardy Medical College, 2013)
Background: Regional metastases to the cervical lymph node is common in laryngeal carcinoma and this is also the most important prognostic factor of the disease. Objective: The purpose of the present study was to see the frequency of cervical metastases related to the sites of laryngeal carcinoma and also to see the relation between primary site and level of metastatic node as well as the relation between T and N stage of the tumour. Methodology: This cross sectional study was done in the Department of Otolaryngology and Head-Neck Surgery at Bangabandhu Sheikh Mujib Medical University, Dhaka and Specialized ENT Hospital of SAHIC, Dhaka from April 2009 to March 2010. A total number of 50 patients who were histopathologically proven laryngeal carcinoma at any age with both sexes were included in this study. General physical examination and ENT examination was done thoroughly. Direct laryngoscopy was done under general anaesthesia to assess the site, size, and extension of the tumour as well as for staging and biopsy. Results: A total number of 60% laryngeal carcinoma patients presented with regional metastases to the cervical nodes. Highest cases among laryngeal carcinoma were supraglottic carcinoma (72.0%) which also showed the highest rate of lymph node metastases (72.2%). Most frequently involved levels of the neck were level II (56.7%) and level III (33.3%). It was also observed that the rate of regional metastases was increasing with the advancing T-stage of the disease. Conclusion: Regional metastases is a useful prognostic indicator of the laryngeal carcinoma. So, early detection of the disease has a great importance on the management of the disease. DOI: http://dx.doi.org/10.3329/jssmc.v4i2.14406 J Shaheed Suhrawardy Med Coll, 2012;4(2):47-49